A low‐frequency variant in SMAD7 modulates TGF‐β signaling and confers risk for colorectal cancer in Chinese population. Issue 7 (6th March 2017) - Li, Jiaoyuan; Zou, Li; Zhou, Ying; Li, Lu; Zhu, Ying; Yang, Yang; Gong, Yajie; Lou, Jiao; Ke, Juntao; Zhang, Yi; Tian, Jianbo; Zou, Danyi; et al.
Abstract : The TGF‐β pathway plays an essential role in regulating cell proliferation and differentiation. GWASs and candidate approaches have identified a battery of genetic variants in the TGF‐β pathway contributing to colorectal cancer (CRC). However, most of the significant variants are common variants and their functions remain ambiguous. To identify causal variants with low‐frequency in the TGF‐β pathway contributing to CRC susceptibility in Chinese population, we performed targeted sequencing of 12 key genes in TGF‐β signaling in CRC patients followed by a two‐stage case‐control study with a total of 5109 cases and 5169 controls. Bioinformatic annotations and biochemical experiments were applied to reveal the potential functions of significant variants. Seven low‐frequency genetic variants were captured through targeted sequencing. The two stage association studies showed that missense variant rs3764482 (c. 83C>T; p. S28F) in the gene SMAD7 was consistently and significantly associated with CRC risk. Compared with the wild type, the ORs for variant allele were 1.37 (95%CI: 1.10‐1.70, P  = 0.005), 1.55 (95%CI: 1.30‐1.86, P  = 1.15 × 10 6 ), and 1.48 (1.29‐1.70, P  = 2.44 × 10 ;8 ) in stage 1, stage 2, and the combined analyses, respectively. Functional annotations revealed that the minor allele T of rs3764482 was more effective than the major allele C in blocking the TGF‐β signaling and inhibiting the phosphorylation of receptor‐regulated SMADs (R‐SMADs). In conclusion, low‐frequency coding variant rs3764482 in SMAD7 is associated with CRC risk in Chinese population. The rs3764482 variant may block the TGF‐β signaling via impeding the activation of downstream genes, leading to cancer cell proliferation, thus contributing to CRC pathogenesis.